An Efficient MAC with Spectrum Handoff and Frame Fragmentation Strategies for Cognitive Radio Networks - AlQahtani, Salman A. (Arabian journal for science and engineering (2011), 2021)
The rapid development of advanced wireless technologies has raised a large demand for spectrum bands. Cognitive radio network (CRN) has been proposed to solve the problem of spectrum scarcity. It enables a set of secondary users (SUs) to use the available spectrum allocated to the primary users (PUs) in an opportunistic way. In fact, there is a lack of in-depth topics in both centralized and distributed cognitive radio models, particularly on the subject of Media Access Control (MAC) protocol. In CRN, the MAC layer is required to perform new functions for efficient usage of spectrum bands. This paper proposes a new CRN MAC protocol to improve the spectrum utilization efficiency that enhances the SUs quality of service (QoS) without interfering the PUs. The main drawbacks of the existing protocols include their weakness in determining the portions of the spectrum that are available, managing the resource access with other users and vacating the occupied resource when a PUs are arrived. To better overcome the shortcomings of the existing protocols and handle the spectrum utilization and SUs QoS, it employs two efficient techniques: the channel handoff and the frame fragmentation. The channel handoff is used for switching the SU between free channels. The fragmentation technique is used to efficiently allow SUs to utilize the smaller spectrum holes. The performance of the proposed protocol is evaluated and compared to the existing basic CRN MAC protocol in terms of total system utilization, SU total loss probability, and SU average waiting time. The results show that the proposed protocol has an advantage over the basic protocol in all scenarios. In addition, it provides a better balance between the SUs QoS improvement and the QoS protection for PUs, while increasing the system utilization beyond 90%.